2022
DOI: 10.3390/nu14214602
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Outcome Measure Data for an Intensive Interdisciplinary Home-Based Pediatric Feeding Disorders Program

Abstract: Background: The purpose of this study was to evaluate the effectiveness of an interdisciplinary home-based feeding program, which is a unique service delivery model. Methods: Data were provided on oral intake, tube feeding elimination, and weight for patients who were dependent on tube feedings (n = 78). Weight data were collected for patients who showed failure to thrive (n = 49). Number of foods consumed and percentage of solids were collected for patients who were liquid-dependent (n = 23), and number of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Crucial to SV, research may lack details on generalization and maintenance (Kennedy, 1992; Ulloa et al., 2019), routine processes (e.g., progressing to portion‐based meals workable in family mealtimes including siblings, guidelines for feeders in other contexts, and eating away from home), and the broader range of goals met, permanent product data, or long‐term improvements in nutrition and quality of life. Moreover, most research has been reported from controlled settings with standardised processes (Sharp et al., 2017; Taylor & Taylor, 2023), and more details are needed on varied processes in translating intensive programmes to home settings (Patel et al., 2022; S. A. Taylor et al., 2019; Taylor et al., 2020). These gaps may limit both researcher's and practitioner's interpretation and utility of the research (Lukens & Silverman, 2014; Sharp et al., 2017; Taylor & Taylor, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Crucial to SV, research may lack details on generalization and maintenance (Kennedy, 1992; Ulloa et al., 2019), routine processes (e.g., progressing to portion‐based meals workable in family mealtimes including siblings, guidelines for feeders in other contexts, and eating away from home), and the broader range of goals met, permanent product data, or long‐term improvements in nutrition and quality of life. Moreover, most research has been reported from controlled settings with standardised processes (Sharp et al., 2017; Taylor & Taylor, 2023), and more details are needed on varied processes in translating intensive programmes to home settings (Patel et al., 2022; S. A. Taylor et al., 2019; Taylor et al., 2020). These gaps may limit both researcher's and practitioner's interpretation and utility of the research (Lukens & Silverman, 2014; Sharp et al., 2017; Taylor & Taylor, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the efficacy of these types of multidisciplinary hospital or clinic‐based day‐ or inpatient‐treatment programs (e.g., Babbitt et al, 1994; Piazza & Carroll‐Hernandez, 2004). More recently the efficacy of an intensive interdisciplinary home‐based program has also been evaluated and shown to have positive treatment outcomes (Patel et al, 2022).…”
mentioning
confidence: 99%